A prospective, split-face, randomized, open-label study comparing efficacy of trichloroacetic acid (100%) and cryotherapy in xanthelasma palpebrarum - Tahir, Moizza; Hafeez, Javeria; Anwar, Muhammad Irfan; Bashir, Uzma; Dar, Nasser Rashid (Journal of Pakistan Association of Dermatologists, 2017)
Objective To compare the clinical efficacy of trichloroacetic acid (TCA) 100% and cryotherapy in xanthelasma palpebrarum (XP). Â Methods 40 patients fulfilling the inclusion criteria were treated with cryotherapy on right eye (group A) and TCA on left eye (group B). Patients were followed up for 6 weeks and final outcome variable of efficacy i.e. complete resolution of xanthelasma was assessed at 6 weeks. Adverse side effects of therapy were also recorded as secondary outcome variables. Â Data were analyzed by SPSS 19.0. Â Results Mean age of patients was 43.75 Â± 5.90 years and age ranged from 34 to 56 years. Out of 40 patients 9 (22.5%) were male and 40 (77.5%) were female. Complete resolution of xanthelasma was seen in only 7 (17.5%) in group A, while complete resolution of lesions was seen in 30 (75%) of patients in group B (p = 0.000). Â Conclusion A single session of 100% TCA is highly effective than cryotherapy in the treatment of Xanthelasma palpebrarum . Â